Pendidikan dan Pelatihan tentang Pengaruh Gizi Seimbang Terhadap Kesehatan Umum dan Rongga Mulut Tim Penggerak PKK Cideng Jakarta Pusat - Cloudya Panjaitan, Caesary; Lestari, Sri; Suwandi, Trijani; Fibryanto, Eko; Livia, Florencia (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Nutrition has an important role during the growth and development of children in general, especially in the oral cavity. Children who are malnourished can cause abnormalities in the hard tissue of the teeth and periodontal. Abnormalities in the oral cavity can disrupt masticatory function, which can affect food intake. Parental knowledge is important in choosing food for the family, because it can affect the nutritional status of children and their families. This Community Service (PkM) were attended by 36 participants from the PKK mobilization team, Cideng, Central Jakarta. The materials provided are the effect of balanced nutrition on general health, the effect of nutrition on the tooth supporting tissue, the impact and prevention of poor dental health and good oral health care in power points, videos and posters. The results of the PkM training were evaluated by a pre-post test using a google form. The evaluation results showed an increase in participants' knowledge scores from an average pre-test score of 45.78 to an average post-test score of 82.19. It is hoped that this PkM activity can increase the knowledge of the PKK mobilization team, so that in the future they can provide education to the public regarding the influence of balanced nutrition on general health and the oral cavity as well as how to maintain oral health.